Profile of Physical Activity Levels of Students in Phase B at Public Elementary Schools in The Ujungberung District - Aziza, Ayyasha Nurul; Lubay, Lukmannul Haqim; Wibowo, Ricky; Budiman, Didin (Indonesian Journal of Sport Management, 2025)
This study aims to analyze the physical activity levels of phase B students in public elementary schools in Ujung Berung District. A quantitative descriptive approach was applied using a survey method. The research population included all phase B students, with the sample determined through total sampling. The instrument used was a validated physical activity questionnaire. The results showed that most students had normal physical activity levels (52.1%), followed by high (26%), low (18.1%), very high (2.8%), and very low (1%). These findings indicate that although the majority of students have normal activity levels, there are still groups that require special attention to improve physical fitness. The study has implications for physical education teachers and parents in encouraging students to engage in regular physical activity. Furthermore, the findings can serve as a reference for future research to further explore the physical activity profiles of elementary school students.